2017
DOI: 10.1371/journal.pone.0176414
|View full text |Cite
|
Sign up to set email alerts
|

Meat consumption is a major risk factor for hepatitis E virus infection

Abstract: BackgroundThe incidence of autochthonous hepatitis E virus genotype 3 (HEV gt3) infections in Western Europe is high. Although pigs are a major reservoir of the virus, the exact sources and transmission route(s) of HEV gt3 to humans remain unclear.MethodsTo determine the role of meat consumption at a population level, the seroprevalence of anti-HEV IgG antibodies was compared between Dutch blood donors with a vegetarian lifestyle and donors who consume meat on a daily basis.ResultsThe age-weighted anti-HEV IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 21 publications
3
28
2
Order By: Relevance
“…The association of HEV seropositivity with age observed in our study has also been reported by others [7][8][9][10][11][12][13][14][15][16][17][18][19][20] and may be explained not only by the cumulative lifetime exposure to HEV, but also by cohort effect, where certain population groups were more likely to be exposed to the virus during their life.…”
Section: Epidemiology and Infectionsupporting
confidence: 90%
See 1 more Smart Citation
“…The association of HEV seropositivity with age observed in our study has also been reported by others [7][8][9][10][11][12][13][14][15][16][17][18][19][20] and may be explained not only by the cumulative lifetime exposure to HEV, but also by cohort effect, where certain population groups were more likely to be exposed to the virus during their life.…”
Section: Epidemiology and Infectionsupporting
confidence: 90%
“…Human HEV infection, investigated using seroprevalence studies, was found to be more prevalent in older ages [7][8][9][10][11][12][13][14][15][16][17][18][19][20], lower socio-economic status [21], poorer residence areas [9,[14][15], among sheltered homeless adults [22] or uneducated people [14], specific nationalities (for example, higher in mixed race donors and ethnic groups within China [12,15], or in immigrants from Afghanistan [14]), drinking water from wells or rivers [15], consumption of meat products [7,15,17,23] especially pork [24,25] and following blood transfusions [1].…”
Section: Introductionmentioning
confidence: 99%
“…For example, porcine blood, which is used in meat production in the Netherlands, has been suggested as a relevant source of HEV infection 21 ; however, meat consumption in general seems to be associated with HEV seroprevalence. 22 Nevertheless, meat is not the exclusive source of infection, as shellfish and berry fruits have been reported to cause HEV infection. 23,24 As HEV infections in the Americas are caused by the HEV genotype 3, this study demonstrates that high socioeconomic and hygienic standards are not sufficiently protective since GT3 infections are mainly foodborne and are not necessarily waterborne.…”
Section: Discussionmentioning
confidence: 88%
“…For future studies, a comparison of anti‐HEV rates in various population subgroups, such as Muslims or vegetarians, would be of interest. For example, porcine blood, which is used in meat production in the Netherlands, has been suggested as a relevant source of HEV infection; however, meat consumption in general seems to be associated with HEV seroprevalence . Nevertheless, meat is not the exclusive source of infection, as shellfish and berry fruits have been reported to cause HEV infection …”
Section: Discussionmentioning
confidence: 99%
“…For example, in a recent study in more than 2,400 individuals living in a livestock‐dense area in the Netherlands, the presence of hepatitis E virus (HEV) antibodies was strongly age related, but not associated with residential proximity to pig farms, suggesting that airborne spread of HEV is unlikely (van Gageldonk‐Lafeber et al, ). The increasing incidence of HEV in Europe is more likely a result of HEV‐contaminated pork consumption (Slot et al, ).…”
Section: Risk Of Zoonotic Infectionsmentioning
confidence: 99%